The Contribution of Speaking Practice with the Native Speaker to Student’s Speaking Ability in Junior High School - Nur Wahyuni; Indah Afrianti (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2021)
Students' speaking ability is not only determined by the teaching and learning process in the classroom, but is also influenced by several factors including: facilities, goals, motivation and learning environment. In this study, researchers used descriptive qualitative research. The subjects of this study were 40 students from class VII SMP PGRI 8 Denpasar. Data collection techniques used in this study were questionnaires, interviews, observation and documentation. Data analysis was obtained after contributing to speaking practice with native speakers in improving students' speaking skills. Based on the results of the study, it was revealed that speaking practice with native speakers made a positive contribution to students' oral production. Conversations with native speakers can increase students' confidence in language, vocabulary and students are also familiar with the expressions used in everyday language, and finally from this research the researcher can find out about students' abilities in: Grammar, Vocabulary, Accuracy and Fluency.